Architecture and Biosynthesis of the Saccharomyces cerevisiae Cell Wall - Orlean, Peter (Genetics Society of America, 2012)
The wall gives a Saccharomyces cerevisiae cell its osmotic integrity; defines cell shape during budding growth, mating, sporulation, and pseudohypha formation; and presents adhesive glycoproteins to other yeast cells. The wall consists of β1,3- and β1,6-glucans, a small amount of chitin, and many different proteins that may bear N- and O-linked glycans and a glycolipid anchor. These components become cross-linked in various ways to form higher-order complexes. Wall composition and degree of cross-linking vary during growth and development and change in response to cell wall stress. This article reviews wall biogenesis in vegetative cells, covering the structure of wall components and how they are cross-linked; the biosynthesis of N- and O-linked glycans, glycosylphosphatidylinositol membrane anchors, β1,3- and β1,6-linked glucans, and chitin; the reactions that cross-link wall components; and the possible functions of enzymatic and nonenzymatic cell wall proteins.